Rancang Bangun Sistem Informasi Reservasi Kamar Homestay Berbasis Web - Anharudin, Anharudin; Susandi, Diki; Saefudin, Saefudin (Teknik Informatika Universitas Pamulang, 2021)
In the current era of globalization, the need for Information Technology is indispensable as a support for business processes, so that with the support of this Information Technology, it will further develop the business that is run. One of the growing lodging businesses is Homestay Wisma Sarang Badak, which is located at Ujung Kulon Pandeglang National Park, Banten-Indonesia. There is still a lack of facilities and infrastructure to support this homestay, especially the limitations of information system-based technology media which have only relied on conventional recording in this case regarding room reservations. From the results of these observations, the idea emerged to research that place. Namely by building a Web-based room reservation information system. To build a room reservation information system, researchers use UML (Unified Modeling Language) as a design tool and use PHP and MySql programming languages as databases. As a result, it is hoped that with this information system, it can make it easier for customers to make room reservations. In addition, Homestay Wisma Sarang Badak can be widely known by the public. And then it can increase the number of customers and can increase income for managers.